2013
DOI: 10.1017/s0022149x1300062x
|View full text |Cite
|
Sign up to set email alerts
|

Parasites of the grouper fishEpinephelus coioides(Serranidae) as potential environmental indicators in Indonesian coastal ecosystems

Abstract: A total of 195 Epinephelus coioides (Hamilton, 1822) were studied for fish parasites from Javanese (Segara Anakan lagoon) and Balinese waters. Up to 25 different parasite species belonging to the following taxa: one Ciliata, one Microsporea, five Digenea, one Monogenea, four Cestoda, four Nematoda, one Acanthocephala, one Hirudinea and seven Crustacea were identified with four new host and locality records. The dominant parasites included the monogenean Pseudorhabdosynochus lantauensis (53.3 -97.1%), the nemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 48 publications
1
44
0
1
Order By: Relevance
“…(4–5) Prevalence of Trichodina sp. because it has been used to estimate bacterial biomass in polluted waters (Kleinertz & Palm, ; Ogut & Palm, ; Palm et al., ) and Cryptocaryon irritans as it has been documented as an indicator for stress and polluted environments (Diamant et al., ; Overstreet, ). Both parasite species (often interacting with stress factors) cause diseases and mortality in intensive grouper culture systems in Asia (Cruz‐Lacierda & Erazo‐Pagador, ; Tonguthai & Leong, ), and consequently are a threat to the health status of the sampled fish.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(4–5) Prevalence of Trichodina sp. because it has been used to estimate bacterial biomass in polluted waters (Kleinertz & Palm, ; Ogut & Palm, ; Palm et al., ) and Cryptocaryon irritans as it has been documented as an indicator for stress and polluted environments (Diamant et al., ; Overstreet, ). Both parasite species (often interacting with stress factors) cause diseases and mortality in intensive grouper culture systems in Asia (Cruz‐Lacierda & Erazo‐Pagador, ; Tonguthai & Leong, ), and consequently are a threat to the health status of the sampled fish.…”
Section: Discussionmentioning
confidence: 99%
“…indet.) were omitted from calculations, since they might represent other recorded taxa (see Kleinertz & Palm, ; Kleinertz et al., ; Palm, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…; and the digenean Didymodiclinus sp.) as an early warning system for environmental changes in Indonesian ecosystem has been reported [98]. Other study has demonstrated that parasites:a) may influence the metabolism of pollutants in infected hosts, b) interact with pollution in synergistic or antagonistic ways, and c) may induce physiological reactions in hosts which were thought to be pollutant-induced [10].…”
Section: Biological Indicators For Environmental Pollutions (General mentioning
confidence: 99%
“…Heavy metal pollution in coastal and marine environments have become a serious threat to the increasingly emphasized to both naturally marine ecosystems and humans who depend on marine resources for food and entertainment industry (Ozden, 2010;Kleinertz and Palm, 2015). They are introduced to coastal and marine environments through a variety of sources and activities including sewage and industrial effluents, coastal modifications and oil pollution (Sale et al, 2010;Irnawati et al, 2014).…”
Section: Introductionmentioning
confidence: 99%